Traumatic Brain Injury: Mechanisms of Glial Response - Mira, Rodrigo G.; Lira, Matías; Cerpa, Waldo (Frontiers in Physiology, 2021)
Traumatic brain injury (TBI) is a heterogeneous disorder that involves brain damage due to external forces. TBI is the main factor of death and morbidity in young males with a high incidence worldwide. TBI causes central nervous system (CNS) damage under a variety of mechanisms, including synaptic dysfunction, protein aggregation, mitochondrial dysfunction, oxidative stress, and neuroinflammation. Glial cells comprise most cells in CNS, which are mediators in the brain's response to TBI. In the CNS are present astrocytes, microglia, oligodendrocytes, and polydendrocytes (NG2 cells). Astrocytes play critical roles in brain’s ion and water homeostasis, energy metabolism, blood-brain barrier, and immune response. In response to TBI, astrocytes change their morphology and protein expression. Microglia are the primary immune cells in the CNS with phagocytic activity. After TBI, microglia also change their morphology and release both pro and anti-inflammatory mediators. Oligodendrocytes are the myelin producers of the CNS, promoting axonal support. TBI causes oligodendrocyte apoptosis, demyelination, and axonal transport disruption. There are also various interactions between these glial cells and neurons in response to TBI that contribute to the pathophysiology of TBI. In this review, we summarize several glial hallmarks relevant for understanding the brain injury and neuronal damage under TBI conditions.